Islam, law, and equality in Indonesia : an anthropology of public reasoning - Bowen, John R. (John Richard), 1951- (Cambridge University Press, 2003)
In Indonesia, the world's largest Muslim-majority country, Muslims struggle to reconcile radically different sets of social norms and laws, including those derived from Islam, local social norms, and contemporary ideas about gender equality and law. John Bowen explores this struggle through archival and ethnographic research and interviews with national figures.